PEMANFAATAN LIMBAH KULIT RAJUNGAN (Portunus pelagicus) SEBAGAI PENYERAP LOGAM BERAT (Pb, Zn, dan Cu) DI PERAIRAN KOLONG PASCA PENAMBANGAN TIMAH INKONVENSIONAL - KHOIRUL MUSLIH; INDRA AMBALIKA (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2011)
Blue swimmer crab (Portunus pelagicus) are not only tasty and popular, these animals are the producers of hard shell to protect their body. From its shell waste, we can harvest chitin and process it into chitosan. As blue swimmer crabs waste is easily found in Bangka, we hope that it can be used to solve water pollution caused by heavy metals (Pb, Zn, and Cu) in many open pit areas there. The objective of this study was to evaluate effectivity of blue swimmer crabs’ chitosan in adsorbing heavy metals. This study was conducted from May to December 2010 in Sungailiat. Contaminated water from ex-mining open pit was used in this study. A 0,5%, 1% and 1,5% of chitosan was applied in degrading heavy metal. Research showed that there was a decline of heavy metal content caused by chitosan application. Its adsorbing activity was influenced by pH and temperature. We can benefit from blue swimmer crabs waste shell to improve water quality in ex-mining open pit water.